The geometry behind the minecraft - Balbino, Marcia Regina; Galante, Edilson; Bonzanini, Taitiâny Kárita (Revista Hipótese, 2020)
This article deals with a pedagogical practice developed in the teaching of Mathematics, together with students of the 6th grade of Elementary School, of a Public School of a municipality in the interior of the State of São Paulo - Brazil. The aim of this activity was to motivate students through the "Minecraft" game, to better understand the planned and three-dimensional (3D) forms. It can be concluded that the use of technological resources in the teaching of geometry motivates and facilitates the understanding of concepts to be constructed by the students, since it contributes to the visualization of the figures, in several formats and plans.
Keywords: Teaching Mathematics; Motivation; Technological Games